Women’s Disengagement Behaviors During Couple Conflict: Investigating Risk Indicators of Intimate Partner Violence - Franz, Molly R. (Journal of interpersonal violence, 2023)
Intimate partner violence (IPV) is a major public health concern, leading to prevention efforts focused on identifying risk indicators of escalating conflict between partners. Certain behaviors during conflict discussions have been uniquely linked to IPV, and there is evidence that disengagement behaviors—an emerging construct—are associated with IPV as well. However, research on disengagement and IPV has largely been limited to self-report, and available observational research is largely cross-sectional. Addressing these limitations, this study prospectively examined the association between observed disengagement behaviors during couple’s conflict discussions and IPV 1 year later, using a sample of 83 heterosexual married or cohabitating partners. Behavioral coding was used to assess each partner’s observed disengagement behaviors and each partner’s psychological and physical IPV was assessed via questionnaire 1 year later. Linear regressions were used to investigate links between indicators of engagement (i.e., listening, questions, eye contact) and psychological and physical IPV perpetration and victimization. Less question asking and higher eye contact by women were associated with greater psychological and physical IPV perpetrated by both women and men 1 year later. Lower listening behaviors by women were associated with greater psychological (but not physical) IPV perpetrated by men 1 year later. In contrast, no disengagement behaviors displayed by men were significantly related to IPV. Applying a latent change score framework using baseline IPV data, findings indicated replicability of results, though with less consistency, suggesting that women’s disengagement behaviors may reflect a larger pattern of abuse that predates and follows disengaged couple interactions. Findings suggest that a unique blend of verbal and nonverbal indicators of women’s disengagement during couple conflict provides a meaningful signal of the emotional climate of the relationship.